The Impact of Organizational Climate and Career Development on Employee Engagement With Personality As A Moderator at PT Kereta Api Indonesia (Persero) - Arifah, Syahdhaniar; Hendarsjah, Hidajat (Jurnal Aplikasi Bisnis dan Manajemen, 2024)
Background: This research aims to investigate whether the organizational environment influences employee engagement, determine whether career development affects employee engagement, and establish whether employee personality can moderate the influence of the organizational environment on employee engagement. Purpose: This study employs a quantitative approach that emphasizes the testing of theories through the measurement of research variables using numerical data and conducting data analysis through statistical procedures. Design/methodology/approach: This study adopts a quantitative approach, emphasizing the testing of theories through the measurement of research variables using numerical data and conducting data analysis through statistical procedures.Findings/Result: The analysis results reveal several differences in variables during validity and reliability tests, as well as hypothesis testing.Conclusion: Based on the conducted analysis, it can be concluded that organizational climate has a negative and insignificant effect on employee engagement, while career development has a positive and significant impact on employee engagement. Furthermore, the dimensions of extraversion, agreeableness, and conscientiousness from the big five personality traits are capable of moderating the influence of organizational climate on employee engagement.Originality/value (State of the art): companies can find out how their workers perceive the career development system that has been implemented in the company and the extent of workers' hopes for an ideal career development system. This can provide an initial idea for companies to be able to formulate policies related to career development systems and research shows that career development systems have a positive effect on employee engagement, which is a benchmark for HR units in particular to focus more on making improvements and improvements in implementation. good career development system. Keywords: big-five personalities, career development, employee engagement, organizational climate, personality